Pengembangan Modul Matematika Berbasis Kontekstual Pada Materi Statistika - Nery, Rieno Septra; Yuliani, Refi Elfira; Heru, Heru; Rofiah, Aslamiati (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2025)
Mathematics is a fundamental science that plays a crucial role in various fields of life and technological development. However, mathematics learning at MI X is still limited to teaching materials provided by the school, making it less engaging and meaningful for students. To address this issue, innovation in learning is needed, one of which is through the development of teaching materials in the form of modules. This study aims to develop a student mathematics module based on a contextual approach for the topic of statistics in Grade IV. The research subjects consisted of 23 students. The development method used is the 4-D model (Define, Design, Develop, Disseminate). The module developed was validated by experts and revised twice until it was deemed suitable for use. Limited trials showed the module's practicality, with a student response percentage of 84.89%. Meanwhile, field trials indicated the module's effectiveness, with an average student learning outcome of 76,2, categorized as excellent. Based on these results, it can be concluded that the contextual-based mathematics module developed is feasible, practical, and has potential effects in improving student learning outcomes in the topic of statistics.